1983
DOI: 10.1159/000249894
|View full text |Cite
|
Sign up to set email alerts
|

Photosensibilisation au carprofène (Imadyl<sup>®</sup>), un nouvel anti-inflammatoire non stéroïdien

Abstract: Carprofen is a new non-steroidal anti-inflammatory drug and a phenylpropionic acid derivative. It seldom causes pruritus, erythema or urticaria. Since 1 year, we have observed 8 photosensitive eruptions associated with Carprofen, a surprising side effect for this group of derivatives. The skin eruption started from 4 days to 3 weeks after the initiation of the treatment and was always limited to the exposed areas of the skin. The eruption was erythematopapular, but also vesiculous or bullous. 2 cases required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 3 publications
1
7
1
Order By: Relevance
“…Because of our findings which appear to differ from that reported by Merol et al [2], we studied the UV absorbance characteristic of carprofen. Carprofen tablets were ground, dissolved in ethanol and filtered.…”
Section: -1contrasting
confidence: 66%
See 2 more Smart Citations
“…Because of our findings which appear to differ from that reported by Merol et al [2], we studied the UV absorbance characteristic of carprofen. Carprofen tablets were ground, dissolved in ethanol and filtered.…”
Section: -1contrasting
confidence: 66%
“…This peak is almost similar to that of benoxaprofen which has an absor bance peak at 310 nm [1], As the action spectrum of the photosensitizer which elicit the clinical reaction in vivo usually coin cides with the absorption spectrum of the compound [3, p. 415] this finding is compat ible to our patients' photosensitivity at the UVB range. It is thus surprising to note pho tosensitization with UVA from carprofen al though in the case of patients with benoxa profen photosensitivity, it was shown that they can respond in a lesser extent to a longer wavelength, too [1], There is a possibility that carprofen can exert its photosensitivity effect through a phototoxicity mechanism as was seen in our patients and also through a photoallergic mechanism as reported earlier [2], It may be important to carry out further in vitro [4,5] and in vivo [1] studies at this juncture to de termine the photosensitizing capacity of car profen, which is chemically related to ben oxaprofen, as necessary precautionary mea sures required for patients who are admin istered this drug instead of benoxaprofen.…”
Section: -1supporting
confidence: 64%
See 1 more Smart Citation
“…1, all of them are 2-arylpropionic acid derivatives. Unambiguous evidence of their photosensitivity side effects has been obtained at the clinical level (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The phototoxic reactions associated with BP, CP, NP, KP, TP and SP usually appear as an exaggerated sunburn characterized by erythema and edema.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions generally occur on exposed skin areas of patients taking ketoprofen, naproxen, tiaprofenic acid and piroxicam (Diffey et al 1983). Carprofen has also been implicated in a more serious photodermatitis (Merot et al 1983). A significant number of cases of benoxaprofen-induced photosensitivity had been reported prior to the withdrawal of this drug from the market (Stern 1983;Stern & Bigby 1984).…”
Section: Cutaneousmentioning
confidence: 99%